Prescription of Physical Activity by General Practitioners in Type 2 Diabetes: Practice and Barriers in French Guiana - Dranebois, Stephanie; Lalanne-Mistrih, Marie Laure; Nacher, Mathieu; Thelusme, Liliane; Deungoue, Sandra; Demar, Magalie; Dueymes, Maryvonne; Drak Alsibai, Kinan; Sabbah, Nadia (Frontiers in Endocrinology, 2022)
Background: General practitioners (GPs) are the major primary healthcare players of the management of type 2 diabetes. In addition to a well-balanced diet, physical activity (PA) appears as a necessary non-medicinal therapy in the management of diabetic patients. However, GPs emphasize several obstacles to its prescription. Aim of this study is to evaluate the practices, the barriers and the factors favoring the prescription of PA in type 2 diabetic patients by GPs in French Guiana. Method: We conducted a cross-sectional descriptive study using a questionnaire, designed to interview 152 French Guiana GPs and describe their practice in prescribing PA in type 2 diabetic patients. Our results revealed that prescription of PA as a non-medicinal therapeutic choice in the management of type 2 diabetes was practiced by 74% of the French Guiana GPs. However, only 37% of GPs responded that they implemented the recommendations, indeed only one third knew about them. The majority of GPs were interested in PA training, but only 11% were actually trained in this practice. The lack of structure adapted to the practice of PA and the lack of awareness of the benefits of PA in metabolic pathology appeared as the main obstacles to PA prescription. Conclusion: This study highlights the importance of improving the training of GPs in the prescription of PA, the development of adapted PA structures and collaboration between the different actors within the framework of sport-health system in type 2 diabetes in French Guiana.